IDENTIFY THE DOMINANT FACTOR OF EMPLOYER BRANDING IN START-UP COMPANY: STUDY CASE TRAVELOKA & TOKOPEDIA - Putri, Sri Nurhajianti; Pritasari, Adita (Journal of Business and Management, 2017)
Abstract. Employer branding is the company image as a ‘great place to work’ in the mind of current potential employee and current employee. Employer branding is strategy to promote a company by creating positive image in order to communicate with job applicants, new employees, and existing employees. Many start-up companies faced the same problem that would be the main caused for why the start-up company could not sustain or growth as well. The problem is the employee did not loyal to the company, high turn-over, the employee used the start-up company to be the ‘miles-stone’ and it is hard to find or attract the potential employee to applied and join them. The purpose of this research is to identify the most important attribute of employer branding looked by the potential employee and current employee, also suggest the solution to improve the way to attract the potential employee and maintain the current employee for start-up company. Online questionnaire with purposive sampling were conducted for data collection. In addition, the researcher used the semi-structured interview with current employees to know deeper about the factor that influenced employer branding.  This research find that Sincerity is the most important attribute for potential employee and good salary is the most important attribute for current employee. Hopefully this research would be beneficial for the human resource or co-founder start-up company to maintain and keep in pace to growth Keywords: Employer branding, Human Resource, Branding, Marketing, Start-up Company